Programa “kayma” para desarrollar la capacidad de indagación en estudiantes del sexto grado de una Institución Educativa Estatal, Trujillo 2018 - Carrion Perez, Milagritos Ney (2019)
This study aims about the influence of the development of the capacity of research in the area of science and technology in students of sixth grade of the educational institution N°80002 “Antonio Torres Araujo” in Trujillo, 2018. Based on a quasi-experimental design, this study was applicated to 37 students in the experimental process and 36 students in the control group. After the application of the pre-test, the result was that the students from the control group and the students from the experimental group have lower percent in the outstanding level than the insufficient level. This study has influenced positively in the students from the experimental group because after the application of the “Kayma” program, the students presented an improvement in the capacity of research as the results were that in the insufficient level was the 38% in the pre-test and 0% in the post test. The approved level is in the 35% in the pre-test and 16% in the post-test. The remarkable level is in the 22% in the pre-test and the 35% in the post-test and finally in the outstanding level is the 5% in the pre-test and the 49% in the post-test. In the control group has shown an advance in the capacity of research, but not in a significant way. In conclusion there was an significant improvement in the development of research of the students mentioned.